Relatively stable response of fruiting stage to warming and cooling relative to other phenological events. Issue 8 (August 2016) - Jiang, L. L.; Wang, S. P.; Meng, F. D.; Duan, J. C.; Niu, H. S.; Xu, G. P.; Zhu, X. X.; Zhang, Z. H.; Luo, C. Y.; Cui, S. J.; Li, Y. M.; Li, X. E.; et al.
Abstract: The timing of the fruit‐set stage (i.e., start and end of fruit set) is crucial in a plant's life cycle, but its response to temperature change is still unclear. We investigated the timing of seven phenological events, including fruit‐set dates during 3 yr for six alpine plants transplanted to warmer (approximately +3.5°C in soils) and cooler (approximately −3.5°C in soils) locations along an altitudinal gradient in the Tibetan area. We found that fruit‐set dates remained relatively stable under both warming and cooling during the 3‐yr transplant experiment. Three earlier phenological events (emergence of first leaf, first bud set, and first flowering) and two later phenological events (first leaf coloring and complete leaf coloring) were earlier by 4.8–8.2 d/°C and later by 3.2–7.1 d/°C in response to warming. Conversely, cooling delayed the three earlier events by 3.8–6.9 d/°C and advanced the two later events by 3.2–8.1 d/°C for all plant species. The timing of the first and/or last fruit‐set dates, however, did not change significantly compared to earlier and later phenological events. Statistical analyses also showed that the dates of fruit set were not significantly correlated or had lower correlations with changes of soil temperature relative to the earlier and later phenological events. Alpine plants may thus acclimate to changes in temperature for their fruiting function by maintaining relatively stable timings of fruit set compared with other phenological events to maximize the success of seed maturation and dispersal in response to short‐term warming or cooling.